An Experimental Therapeutics Focus on Novel Mechanistic Targets in Cognitive Behavioral Treatments: Introduction to the Special Section. - Otto, Michael W.; Birk, Jeffrey L. (Behavior Therapy, 2023)
• This is the introductory article for a special section on mechanistic science. • The NIH Science of Behavior Change (SOBC) program offers an approach for this science. • Articles highlight research reflecting the recommended SOBC developmental progression. This article introduces the special section, "An Experimental Therapeutics Focus on Novel Mechanistic Targets in Cognitive Behavioral Treatments." The purpose of this special section is to highlight research that follows the recommended Science of Behavior Change (SOBC) developmental progression for an experimental medicine approach to identifying and testing mechanisms of behavior change. Emphasis was placed on the earlier stage "pipeline" of investigations of novel mechanisms for behavior change: mechanisms that are undergoing the initial stages of validation. In this series, seven empirical articles are presented and are followed by an article detailing a checklist for reporting mechanistic research studies in order to improve communication of findings in the field. The final article in this series discusses the history, current status, and future directions for the SOBC approach to mechanistic science as viewed by National Institute of Health program officials.